Diversity as Polyphony: Reconceptualizing Diversity Management from a Communication-Centered Perspective - Trittin-Ulbrich, Hannah (Journal of business ethics, 2017)
In this paper, we propose reconceptualizing diversity management from a communication-centered perspective. We base our proposal on the observation that the literature on diversity management, both in the instrumental and critical traditions, is primarily concerned with fostering the diversity of organizational members in terms of individual-bound criteria (e.g., gender, age, or ethnicity). By drawing on Bakhtin’s notion of polyphony as well as the ‘communicative constitution of organizations’ (CCO) perspective, we suggest reconsidering diversity as the plurality of ‘voices’ which can be understood as the range of individual opinions and societal discourses that get expressed and can find resonance in organizational settings. We contribute to the literature on diversity management by moving away from a focus on individual-bound and inalterable criteria of diversity and toward a reconceptualization of diversity management as dynamic processes of voice articulation and mediation.